Patterns of Help-seeking Strategies in Response to Intimate Partner Violence: A Latent Class Analysis - Cheng, Shih-Ying (Journal of interpersonal violence, 2022)
Women engage in multiple strategies to cope with the impact of intimate partner violence (IPV). Prior research has focused predominantly on women?s service utilization and help seeking as individual acts, yet it is likely that women engage in distinct patterns of multiple help-seeking strategies to achieve safety. As such, the current article examines patterns of service-related help-seeking strategies survivors employ. This article also investigates demographic factors, relationship characteristics, and mental and physical health effects of IPV associated with patterns of help seeking. Using a web-based survey, data were collected from service-engaged adult female IPV survivors (n = 369) in the Southwest region of the United States. Latent class analysis (LCA), a person-centered analytical approach, was used to identify survivors? patterns of help seeking. A 3-class LCA model was determined to be the best fit for the data. Among the sample, 50% of women broadly engaged formal and informal networks, 15% primarily engaged informal networks, and 35% broadly engaged networks but avoided legal systems while seeking other formal services. Findings indicated varying and significant associations between class membership and race/ethnicity, foreign-born status, number of children, IPV severity, and mental health symptoms. The findings reinforce the need for practitioners to be aware of the varied ways women choose or avoid seeking help and explore women?s preferences. Comprehensive and collaborative service networks are necessary for early detection and holistic care. Addressing structural factors is imperative for expanding the range of viable support options available to IPV survivors, particularly women of color.